Variant-specific RT-qPCR for rapid screening of B.1.617 mutations in SARS-CoV-2. Issue 1 (31st December 2022) - Jallul, Mwada; Ibrahim, Khaled; Zaghdani, Ahmed; Abdusalam, Mohamed Musbah; Al Dwigen, Samira M; Atwair, Wafya S; Elbasir, Mohamed; Alhudiri, Inas; El Meshri, Salah Edin; Elzagheid, Adam
ABSTRACT: The continuous emergence of new SARS-CoV-2 variants required rapid and reliable diagnostic methods for early detection and monitoring of the spread of the virus, especially in low-resource countries where whole genome sequencing is not available. We aimed to evaluate and compare the performance of two different RT-qPCR screening assays for the detection of B.1.617 lineage mutations. A total of 85 SARS-CoV-2 positive samples were collected between 9 th August and 10 September 2021 and screened by two mutation-specific RT-qPCR assays for simultaneous detection of B.1.617.1 and B.1.617.2 lineage mutations. VIASURE Variant II PCR assay identified 2 Delta variant-specific mutations (L452R, and P681 R) in 80% of tested samples, while the PKamp™ Variant Detect™ assay was only able to detect one Delta variant specific mutation (L452R) in 75% of tested samples. This is the first report to show the Delta variant as the cause of the third wave in Libya. The use of multiplex RT-qPCR assays has allowed the identification of new variants for rapid screening. However, RT-qPCR results should be confirmed by whole genome sequencing of SARS-COV-2.